Bioecology And Life-Tables Of The Pea Aphid Aphis Craccivora Koch. and Its Natural Enemies - Reji Rani OP (Department of Agricultural Entomology, College of Agriculture, 1995)
The seasonal distribution of pea aphid Aphis craccivora and its predators on twigs and pods of cowpea and a perennial alternate host of the insect, glyricidia were assessed during 1993 – 94 at the College of Agriculture, Vellayani, Kerala. On cowpea peak population of the pest during the first season, on twig and pods were noted in January / February while on glyricidia two peaks were noted in the season first from December and early February and the next from February to end to early March. In the second season also one peak period each were seen on twigs and pods of cowpea and on glyricidia, but the three did not coincide in the periods of occurrence. In glyricidia a fourth peak was observed in August / September 1994. Studies thus revealed vital indifference in the trend of population build up on cowpea and glyricidia and even on the twigs and pods of the same plant. The growth stages of the crops and their nutritive status are suggested as the major factor influencing the population build up of A. craccivora than any other factor in the ecosystem. Survey of natural enemies in the region revealed the occurrence of six predators and one insect pathogen. Among them C. sexmaculata and x. scutellare were found to be the important ones. A pest dependent increase in the population of predators were observed but the trends of the population build up of the pest and the natural enemies did not show any effective role of the predators in suppressing the pest population under field condition. The detailed biology of A. oraccivora and the two predators were studied in the laboratory conditions. The duration and percentage survival of each larval instar, adult longevity and fecundity were studied and the data indicated that short duration and higher fecundity od A. craccivora when compared to predators account for the successful establishment of the pest in field even with higher levels of predator population. The parameters of biology in laboratory were found more favourable for the population of X. scutellare than for C. sexmaculata. But in field latter was more successful. Feeding potential of C. sexmaculata ( larvae and adult) was much higher than that X. scutellare (larvae) only. Hence C. sexmaculata was found to be a better bicontrol agent for the control of A. craccivora. The exhaustive information gathered will be useful in cinstructing models for integrated pest control programmes of A. craccivora. Age specific life-tables were consctucted for A. craccivora for assessing the intrinsic rate of increase and germination time of pest and these were found suitable for fast population build up. Life tables were prepared during, December 1993 and January 1994 and the ‘Generation survival’ and ‘Trend Index’ were found increasing in January. The lower mortality percentage of the late instar nymphs were found as the reason for the variations. But the mortality factors could not be precisely determined in the investigations. Series of such life tables developed for different seasons, hosts and different ecosystems may be necessary for constructing suitable models for integrated pest management practices.